EFL Students' Perception on Using Mobile Learning Applications for Learning to Write - Rohmah, Anifatur; Iftanti, Erna; Shofiya, Arina (FOSTER: Journal of English Language Teaching, 2023)
One way to aid in English learning is mobile learning. The main features of the mobile learning application are simplicity, engagement, and instant sharing. Mobile learning also has the potential to make learning to spontaneous, anywhere, and adapted to the wishes of the teacher or students (Miangah and Amin Nezarat, 2012). The objective of this study is to know what EFL Students’ Perception on Using Mobile Learning Application for Learning to Write. This study used descriptive quantitative research with survey design. To collect the data of the research, the data were collected through questionnaire. The population were EFL Students and sample of the study were 56 students. From the data analysis, it could be concluded that there were positive and negative perceptions among EFL Students. The total number of positive perceptions was 77%. Meanwhile, 23% students have negative perceptions. Mobile learning application used by EFL Students include Edmodo (11%), Google Classroom (36%), Google Meet (18%), Twitter (7%), and Quiz (28%). The most dominant Mobile Learning Application is Google Classroom.